An in vitro comparison of zinc phosphate polycarboxylate and glass ionomer cements in the retention of orthodontic bands - De Leon, Josephine Ann Marie Y.; Mack, Carolyn O.; Macasaet, Avelino (Adviser).
The ability to retain the cast restorations or orthodontic band, as the case may be, is among the more favorable properties sought after in a dental luting cement. Zinc phosphate is the most popular material used to cement orthodontic bands today. However, decalcification of enamel immediately surrounding the area of the cemented band has precipitated the use of fluoride containing dental cements such as polycarboxylate and glass ionomer cements. These two cements have the added advantage of being able to adhere to enamel. This study will, therefore, compare the retention of orthodontic bands using these three cements. Forty-five extracted human molars, sound on their buccal, lingual and proximal surfaces were mounted on blocks. Orthodontic bands (.006x.160 in.) were fitted on each tooth hand handles were welded on each side. Zinc phosphate, polycarboxylate and glass ionomer cements were used to cement fifteen bands each. A Universal Testing Machine was then employed to measure the force required to unseat the band. Applying the force measurement to the surface area covered, the resultant stress served as the gauge of the retentive strength of the cement. Results showed zinc phosphate yielded ionomer cement. However, no significant difference was found among the three groups. Correlating the site of bond failure with the kind of cement by assessing visually the type of failure mode, a definite relationship was established.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental glass ionomer cements; Zinc phosphate polycarboxylate